The Effect of Brand Image and Product Quality on Purchase Decisions of Frozen Food Products with Purchase Interest as an Intervening Variable on Consumers of PT Madusari Nusaperdana in Medan City - Willy Zek Nasution; Yossie Rossanty; Dewi Nurmasari Pane (Utan Kayu Publishing, 2026)
This study aims to analyze the effect of brand image and product quality on frozen food purchase decisions, with purchase intention as an intervening variable among consumers of PT Madusari Nusaperdana in Medan City. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to consumers who had purchased products from PT Madusari Nusaperdana and were analyzed using regression analysis and mediation testing to examine both direct and indirect effects among variables. The results indicate that brand image and product quality have a positive and significant effect on purchase intention and also exert a positive and significant effect on purchase decisions. Furthermore, purchase intention is found to have a positive and significant effect on purchase decisions. Mediation analysis confirms that purchase intention mediates the relationship between brand image and product quality and purchase decisions. These findings suggest that strengthening brand image and improving product quality can enhance consumers’ purchase intention, which in turn leads to higher purchase decisions for frozen food products. The practical implication of this study highlights the importance of consistent brand-building strategies and quality control in increasing a company’s competitiveness.